Region- and Cell-Specific Expression of Transmembrane Collagens in Mouse Brain - Monavarfeshani, Aboozar; Knill, Courtney N.; Sabbagh, Ubadah; Su, Jianmin; Fox, Michael A. (Frontiers in Integrative Neuroscience, 2017)
Unconventional collagens are nonfribrillar proteins that not only contribute to the structure of extracellular matrices but exhibit unique bio-activities. Although roles for unconventional collagens have been well-established in the development and function of non-neural tissues, only recently have studies identified roles for these proteins in brain development, and more specifically, in the formation and refinement of synaptic connections between neurons. Still, our understanding of the full cohort of unconventional collagens that are generated in the mammalian brain remains unclear. Here, we sought to address this gap by assessing the expression of transmembrane collagens (i.e. collagens XIII, XVII, XXIII, and XXV) in mouse brain. Using quantitative PCR and in situ hybridization, we demonstrate both region- and cell-specific expression of these unique collagens in the developing brain. For the two most highly expressed transmembrane collagens (i.e. collagen XXIII and XXV), we demonstrate that they are expressed by select subsets of neurons in different parts of the brain. For example, collagen XXIII is selectively expressed by excitatory neurons in the mitral / tufted cell layer of the accessory olfactory bulb and by cells in the inner nuclear layer of the retina. On the other hand, collagen XXV, which is more broadly expressed, is generated by subsets of excitatory neurons in the dorsal thalamus and midbrain and by inhibitory neurons in the retina, ventral thalamus, and telencephalon. Not only is col25a1 expression present in retina, it appears specifically enriched in retino-recipient nuclei within the brain (including the suprachiasmatic nucleus, lateral geniculate complex, olivary pretectal nucleus and superior colliculus). Taken together, the distinct region- and cell-specific expression patterns of transmembrane collagens suggests that this family of unconventional collagens may play unique, yet-to-be identified roles in brain development and function.